Voorreformatorische koorhekken in Nederland - Kroesen, Justin (Jaarboek voor liturgieonderzoek, 2005)
This article presents a survey of extant choir screens in the Netherlands, with a special emphasis on their decoration and imagery. Compared to the surrounding countries, the Calvinist Netherlands are quite rich in pre-Reformation choir screens. In 23 churches examples have been preserved wholly or in part, mainly in the provinces of North and South Holland. The screen-prpe of a wooden frame filled with metal trellice-work is hardly found outside the country, so that we can speak of a genuine Netherlandish genre. The relatively high number of preserved Dutch choir screens can be ascribed to a certain ‘preserving power of Calvinism’: while the Protestants thoroughly removed all altars and images from their churches, other pieces offurniture were often left intact. A choir screen, unless decorated with explicitly Roman-Catholic symbols, served as a natural backdrop for the nave and separated the preaching area from the choir, which had now fallen out of use.